Self-efficacy and anxiety and depression in patients with colostomy - Gapińska, Bożena; Tartas, Małgorzata; Walkiewicz, Maciej; Majkowicz, Mikołaj (Contemporary Oncology/Współczesna Onkologia, 2008)
Surgical intervention leading to the creation of a colostomy seems to be a critical experience for the patient. Having an abdominal anus impairs the quality of human life, as well as the individual’s abilities to adjust to a new reality. The main aim of the research was to describe the self-efficacy factor (which could be a predictor of how patients can defeat cancer), sex, education, period of time the colostomy had existed, the number of hospitalizations and also depression and anxiety in patients with colostomy. The research was conducted on a group of 65 patients who were hospitalized in the General Surgery Department of St. Wojciech Hospital in Gdańsk and the General Surgery and Gastroenterology Department of J. Budziński Hospital in Gdynia after operative procedures, as a consequence of which the abdominal anus was created. The research was based on the prepared questionnaire and Sherer’s Self-Efficacy Scale, Beck’s Depression Scale and Spielberger’s State-Trait Anxiety Inventory. The results show that there is no significant relation between the level of self-efficacy and sex, education or period of time the colostomy had existed. There is a significant relation between self-efficacy and the number of hospitalizations of the patient. The number of hospitalizations and operations correlates with self-efficacy negatively. The results could lead to the conclusion that men who have higher levels of anxiety trait and anxiety state are less motivated for treatment, cope with failures worse and are less convinced about the opportunity to cope with cancer.